2022
DOI: 10.3390/vetsci9040191
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Pituitary Apoplexy: Clinical Presentation, Diagnostic Imaging Findings and Outcome in 19 Dogs

Abstract: In human medicine, pituitary apoplexy (PA) is a clinical syndrome characterised by the sudden onset of neurological signs because of haemorrhage or infarction occurring within a normal or tumoral pituitary gland. The diagnosis is usually performed combining neurological signs and imaging findings. The aim of the present study is to describe the abnormal neurological signs, the diagnostic imaging findings, based on Computed Tomography (CT) and/or Magnetic Resonance Imaging (MRI), and the outcome in a population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 36 publications
6
17
4
Order By: Relevance
“…In recent years, cases of pituitary macroadenomas secondary to PTA have been reported in veterinary medicine; however, no effective treatment has been identified, and no case of surgical intervention with long-term prognostic follow-up has been reported [8,[10][11][12]. In the present case, T2*-weighted MRI on day 52 showed that the hemorrhage was concentrated in the dorsal portion of the pituitary tumor [22], and the ACTH concentration measured on day 51 was similar to that on day 9, suggesting that the ventral pituitary tissue maintained ACTH production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, cases of pituitary macroadenomas secondary to PTA have been reported in veterinary medicine; however, no effective treatment has been identified, and no case of surgical intervention with long-term prognostic follow-up has been reported [8,[10][11][12]. In the present case, T2*-weighted MRI on day 52 showed that the hemorrhage was concentrated in the dorsal portion of the pituitary tumor [22], and the ACTH concentration measured on day 51 was similar to that on day 9, suggesting that the ventral pituitary tissue maintained ACTH production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of cases of PTA due to pituitarydependent hypercortisolism (PDH) caused by pituitary macroadenomas have been reported in dogs [10][11][12]. In eight of these cases, the dogs were euthanized due to severe seizures or death during computed tomography imaging [10][11][12].…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] A recent case series of 19 dogs (including 2 of the previously reported 6 dogs) described mainly altered mentation, vestibular dysfunction and seizures. 15 While computed tomography, histopathology, and postmortem findings are described in this literature, in addition to magnetic resonance imaging (MRI) findings of pituitary apoplexy in a cat, 16 published MRI findings in dogs with pituitary apoplexy appear to be limited to 8 cases. 14,15 Treatment options and outcome data are also limited in the veterinary literature, as many dogs are euthanized at the time of diagnosis or fail to survive to hospital discharge.…”
Section: Introductionmentioning
confidence: 99%